1996
DOI: 10.1073/pnas.93.16.8502
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of glioblastoma angiogenicity and tumorigenicity by inhibition of endogenous expression of vascular endothelial growth factor.

Abstract: The development of new capillary networks from the normal microvasculature of the host appears to be required for growth of solid tumors. Tumor cells influence this process by producing both inhibitors and positive effectors of angiogenesis. Among the latter, the vascular endothelial growth factor (VEGF) has assumed prime candidacy as a major positive physiological effector. Here, we have directly tested this hypothesis in the brain tumor, glioblastoma multiforme, one ofthe most highly vascularized human cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
157
1
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(165 citation statements)
references
References 35 publications
5
157
1
2
Order By: Relevance
“…Thus, it is quite possible that inactivation of THBS1 involves multiple mechanisms in GBM, and it would be interesting to determine whether THBS1 methylation correlates with P53 mutations (or lack thereof) or chromosome 10 allelic status in GBM. In addition, it would be interesting to compare THBS1 methylation with the expression of other angiogenic factors in GBM such as VEGF (Cheng et al, 1996;Plate et al, 1992) and/or a P53 regulated angiogenesis inhibitor that appears to be distinct from THBS1 (Van Meir et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is quite possible that inactivation of THBS1 involves multiple mechanisms in GBM, and it would be interesting to determine whether THBS1 methylation correlates with P53 mutations (or lack thereof) or chromosome 10 allelic status in GBM. In addition, it would be interesting to compare THBS1 methylation with the expression of other angiogenic factors in GBM such as VEGF (Cheng et al, 1996;Plate et al, 1992) and/or a P53 regulated angiogenesis inhibitor that appears to be distinct from THBS1 (Van Meir et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, even a twofold change in the activity of the VEGF promoter may in itself have biological relevance. For example, 2 ± 3-fold reductions in VEGF expression in tumor cells have been shown to produce surprisingly profound suppressive e ects on tumor angiogenesis and tumor growth in vivo (Ferrara et al, 1996;Cheng et al, 1996;Okada et al, 1998;. In HPV-16-positive cells where other genetic and epigenetic changes (e.g.…”
Section: Hpv-16 E6 Oncoprotein and Vegf In Tumor Angiogenesismentioning
confidence: 99%
“…The ability of a VEGF antisense construct to reduce angiogenicity and tumorigenicity of human U87MG GBM cells suggested that VEGF plays a key role in glioma development. 3 In human brain cancers, a close correlation was found between VEGF expression, tumor vascularization and grade of malignancy, 4 with 95% of GBMs staining positive for VEGF. 5 The signals were localized in both perinecrotic and vital tumor areas suggesting that both hypoxia and other stimuli may control the expression of VEGF in gliomas.…”
mentioning
confidence: 99%